Effect of sitting postures and shoulder position on the cervicocephalic kinesthesia in healthy young males. (2nd April 2016) - Alghadir, Ahmad; Zafar, Hamayun; Iqbal, Zaheen; Al-Eisa, Einas
Abstract: Information about head orientation, position, and movement with respect to the trunk relies on the visual, vestibular, extensive muscular, and articular proprioceptive system of the neck. Various factors can affect proprioception since it is the function of afferent integration, and tuning of muscular and articular receptors. Pain, muscle fatigue, and joint position have been shown to affect proprioceptive capacity. Thus, it can be speculated that changes in body posture can alter the neck proprioception. This study was undertaken to investigate the effect of body posture on cervicocephalic kinesthetic sense in healthy subjects. Cervicocephalic kinesthetic sensibility was measured by the kinesthetic sensibility test in healthy young adults while in (a) habitual slouched sitting position with arms hanging by the side (SS), (b) habitual slouched sitting position with arms unloaded (supported) (SS-AS), and (c) upright sitting position with arms hanging by the side (US) during maximum and 30 degree right, left rotations, flexion, and extension. Thirty healthy male adults (mean age 27.83; SD 3.41) volunteered for this study. The least mean error was found for the SS-AS position (0.48; SD 0.24), followed by SS (0.60; SD 0.43) and US (0.96; SD 0.71), respectively. For all test conditions, there was significant difference in mean absolute error while head repositioning from maximum and 30 degree rotation during SS and SS-AS positions ( p  < 0.05). In conclusion, body posture can affect the proprioception function of the neck. Supporting the upper extremities in such a way that their weight is unloaded, which leads to reduction in the tension between the neck and shoulder girdle, can improve cervicocephalic kinesthetic sense in both the horizontal and vertical planes. The findings of this study can be implemented in people who have to do repeated arm and neck movements, by using ergonomically effective chairs with proper arm supports. This might help in prevention and treatment of neck pain.